Ketika Harta dan Hiburan Jadi Tolok Ukur Bahagia: Refleksi Agama terhadap Fenomena Konsumerisme dan Hedonisme - Shafira Nailah Fakhirah; Davina Nisya Al Bahri; Nadia Nur Faizah; Reyvan Muhammad; Abdul Fadhil (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The phenomenon of consumerism and hedonism increasingly dominates modern society, where wealth and entertainment are often used as the benchmark of happiness. A materialistic lifestyle and the pursuit of temporary pleasures lead to moral degradation, weaken spirituality, and shift fundamental human values. This article examines these phenomena from a religious perspective, particularly Islamic teachings, which emphasize life balance, simplicity, and true happiness based on faith. Through a literature review and theological reflection, the article reveals that consumerism and hedonism arise due to weak self-control, lack of spiritual awareness, and the influence of global culture that promotes an instant lifestyle. Religion offers solutions through the concepts of zuhd (avoiding excessiveness in worldly matters), qana’ah (contentment), and tazkiyatun nafs (purification of the soul) as paths to genuine happiness. The conclusion suggests that materialistic happiness is temporary, while spiritual happiness based on faith and morality is deeper and more sustainable. Therefore, strengthening religious values and self-awareness is essential to enable society to live proportionally, avoid falling into consumptive and hedonistic lifestyles, and return to the true essence of happiness.